Length-Weight Relationship and Condition Factors of Mullet Fish (Mugil cephalus) Caught at the Waters of Ngurah Rai Grand Forest Park, Bali - Putra, Dewangga Ari Kusuma; Restu, I Wayan; Kartika, I wayan Darya (Advances in Tropical Biodiversity and Environmental Sciences, 2021)
Grey Mullet fish ( Mugil cephalus ) is one of the economically valuable fish in the waters of the Ngurah Rai Forest Park, Bali. This study was conducted to examine the relationship between the length and weight of the condition of Belanak fish caught in the waters of the Ngurah Rai Forest Park, Bali. The purpose of this study was to determine the description of the growth conditions of Belanak in the waters of Ngurah Rai Tahura, Bali will create a plan for sustainable management of Belanak Fish resources. Sampling was conducted in March 2019 to May 2019. Data analysis used was the relationship between length and weight and condition factors. Data processing is done by using the Microsoft Excel program. The results obtained showed that the mullet fish has a negative allometric growth pattern (long growth is faster than weight growth) equation W = 0.011 L 2.195 and the coefficient of determination (R 2 ) of 0.75 (75% growth in weight is influenced by growth long). Belanak fish caught in Ngurah Rai Tahura waters have a condition factor value (K value) ranging from 0.941 to 1.514 which indicates that Belanak is in good condition and is in its infancy.